Manajemen Pengembangan Kapasitas pada Sekolah Unggulan - Junaris, Imam (Institut Agama Islam Negeri (IAIN) Tulungagung, 2017)
Management of capacity development refers to a process in which individual, group, organization, institutional, and society develop their potential both individually and collectively to implement their function, solve their problem, achieve their targets individually in the effort of establishing excellent schools. By the of a program coherence dimension in the context of school capacity development, this qualitative study is conducted at the State Junior High School 1 Tulungagung. The research results reveal that both of the schools have formulated the planning of institutional capacity development as a reference in actuating and evaluating of the school capacity development to perform excellent school profile. The planning of capacity development at excellent schools is just a dream and together with the schoolsâ stakeholdersthe built planning for school institutional development is formulated. The formulation is in the forms of schoolâs work planning, annual work planning, or activity program planning and school budgeting. The implementation of the capacity development at excellent schools is initiated by preparing human resource quality and school infrastructure. Meanwhile, the evaluation of the capacity development at excellent schools is done by conducting a supervision to observe the appropriateness between both planning and the action and between planning and the achieved results. If the predetermined of standard indicatorshave been achieved and even they exceed to the indicators, it can be stated that the development of school institutional capacity must be achieved as well.